2021
DOI: 10.5173/ceju.2021.0264
|View full text |Cite
|
Sign up to set email alerts
|

Endourological management of encrusted ureteral stents: An up-to-date guide and treatment algorithm on behalf of the European Association of Urology Young Academic Urology Urolithiasis Group

Abstract: Encrustation of ureteral stents can represent a complex challenge. Patients can require multiple intervention types as well as several operative sessions. Our aim was to establish a practical guide for managing such cases as well as an accompanying treatment algorithm. Nearly all cases can now be successfully managed with minimally invasive methods such as ureteroscopy and/or percutaneous nephrolithotomy. Use of a validated tool for grading burden of encrustation is recommended. Careful patient counselling as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In case of stone burden in renal pelvis, it can be treated by RIRS or PCNL. Endoscopic combined intrarenal surgery (ECIRS) may be preferred in cases of high encrustation and stone burden in the ureter and renal part (6,10). Today, although the rates of endourological approaches have increased, open surgery is still a good option in difficult cases (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In case of stone burden in renal pelvis, it can be treated by RIRS or PCNL. Endoscopic combined intrarenal surgery (ECIRS) may be preferred in cases of high encrustation and stone burden in the ureter and renal part (6,10). Today, although the rates of endourological approaches have increased, open surgery is still a good option in difficult cases (1).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of forgotten dj stents can sometimes be difficult and complicated for urologist depending on the degree of encrustation and the complications (1,6). Percutaneous nephrolithotomy (PCNL), ureteroscopy (URS), retrograde intrarenal surgery (RIRS), transuretral cystolithotripsy and the combine surgeries can be used for removal of encrusted stents.…”
Section: Introductionmentioning
confidence: 99%
“…Multimodal surgery is generally required. A systematic review on behalf of the EAU YAU Urolithiasis Group revealed that 27% of the encrusted stents require a combined surgery, followed by 24% of URS alone or 19% of SWL alone as a single surgery ( 29 , 30 ). Because of the short indwelling time, the encrustations included in our study are principally low or median degrees by three evaluation tools, which are not easily identifiable.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, PCN or ureteral stent insertion has also been adopted to manage all patients with symptomatic KSD diagnosed during pregnancy where conservative measures have failed. However, it is problematic as the greater rates of encrustation in pregnancy often require stent exchange every 4 to 6 weeks [37]. PCNs and indwelling ureteral stents can also have a deleterious effect on quality of life.…”
Section: Temporising Measuresmentioning
confidence: 99%